The Qatar-Nepal Remittance Corridor : Enhancing the Impact and Integrity of Remittance Flows by Reducing Inefficiencies in the Migration Process - Endo, Isaku; Afram, Gabi G. (World Bank, 2012)
Remittance inflows play a crucial role in Nepal's economy. Officially recorded remittances already amounted to almost a quarter of the Gross Domestic Product (GDP) in 2009. The 2008-09 global economic crises resulted in slower growth of remittance inflows in Nepal, leading directly to lower disposable income. This is a telling reminder of the importance of promoting a supportive environment for remittances. Nepali migration continues to increase as workers seek greater economic opportunities abroad. In this quest, Qatar is one of the important migration destinations for Nepali migrant workers. This report analyzes the migration and remittance transfer processes in the Qatar-Nepal Corridor in order to provide policy recommendations that would help improve the scale and impact of remittance transfers from Qatar to Nepal, and enhance the efficiency and integrity of migration and remittances in the corridor. The report identifies challenges in the migration process from Nepal to Qatar (related to high migration costs and their financing) and constraints in the remittance transfer process from Qatar to Nepal, which together limit the development and poverty reduction impact of remittance flows to Nepali households. As this report highlights, the Qatar-Nepal remittance corridor has several distinctive features. First, the majority of remittance flows from Qatar to Nepal are being transferred through officially regulated remittance channels. One of the reasons for this is actually the second feature of this corridor, namely, the officially managed migration process from Nepal to Qatar (as a result of which the majority of migrants are documented workers). The third feature is the contrast between the high competition and low prices of remittance services in this corridor on the one hand, and the contradictory rules and high costs incurred during the migration process on the other hand. Finally, as a by-product of the complex migration process which involves multiple players, financial transfers through informal mechanisms take place from Nepal to Qatar in order to pay the commissions of manpower agencies and middlemen.